Effect of high pressurized sterilization on oil palm fruit digestion operation - Noerhidajat,; Yunus, Robiah; Zainal Abidin, Zurina; Syam, Syafiie; Ramanaidu, V.; Rashid, Umer (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Sterilization and digestion are two important steps in the palm oil milling process prior to oil extraction. After sterilization, palm fruitlets are stripped and then fed into a digester where the fruitlets are heated with atmospheric pressure steam to soften and loosen the mesocarp fiber. The effect of different pressures of sterilization on digestion operation needs to be investigated. To convey better understanding of the process, several tests were performed on the fruitlets sterilized under different sterilization conditions, i.e., 40 and 70 psi. Oil released, sludge formation and water absorption during the digestion process were analyzed. It was found that fruitlets sterilized at 70 psi contained more sugar content in the condensate due to more hydrolyzed sterilized fruit. It was also found that fruit sterilized at higher pressure released more oil into the condensate and absorbed more water.